Alleviation of cold stress induced oxidative stress in White Leghorn Chicken by Chromium and Vitamin C supplementation - Mayengbam, Prava; Ali, M Ayub; Lallianchhunga, M C; Tolenkhomba, Thingujam Chaa; Goswami, Ranjan; KHUKHODZIINAI, J S; RANJANA (The Indian Journal of Animal Sciences, 2022)
White Leghorn layer chicken experienced cold stress during December, 2019 to January, 2020 with lowest minimum AT and lowest average temperature during later part of January, 2020. Cold stress caused increase in HSP70 and SOD of White Leghorn layer chicken. Supplementation of chromium picolinate (@ 400 μg/kg feed) and vitamin C (@ 250 mg/kg of feed) alleviated cold stress and cold induced oxidative stress in White Leghorn chicken. Alleviation of stress by supplementation of chromium picolinate and vitamin C could be estimated by the measure of drop in HSP70 and SOD. Supplementation of chromium picolinate and vitamin C also had beneficial impacts on egg length during cold stress. Combination of chromium picolinate and vitamin C was best to alleviate cold stress while vitamin C was best to lower oxidative stress in layer.